Définir un cadre méthodologique commun en cartographie participative - Marie-Christine Cormier-Salem; Tidiane Sané (Revue d'ethnoécologie)
The aim of this article is to show the collective multi-partnership dynamics, inspired by the participatory mapping workshop organized in the rural community of Diembéring in Casamance, in southwest Senegal, in July 2014. The purpose of this workshop was to understand the past and present organization of the village’s spaces and the uses of maps of the “terroirs”, or communal territories, made by and with the local people of three localities of this rural community: Diembéring, Bouyouye and Cabrousse.This workshop brought out the traditional knowledge and know-how of the local people in terms of representation of their spaces, but it also highlighted issues that are often difficult to apprehend, such as tenure conflicts. Coupled with other tools of field surveys (interviews, transects, historical profiles, agricultural calendar, etc.), participatory mapping pointed out the rice farming crisis in Casamance and its profound socio-cutural consequences on the Joola communities.Beyond the production of maps and new co-constructed knowledge, this workshop led to explicitly formulate the needs of the local people and their questions about the future of their terroirs and to accompany them in their advocacy (commitment of multidimensional dialogue) with the local or deconcentrated authorities of the Senegalese State. It also was the occasion to ask scientific and technical experts about their intellectual posture, and their commitment to applied research.